Redes de produção e dinâmica na organização das espacialidades - Baréa, Neiva Marli Martins dos Santos (2008)
Net relationships are coordinated by the action of participants interconnected in many scales and geographic spatiality; in a social, political, economic, and solidarity character. The rural space presents a complexity of processes from such relationships in the 21st Century, with production restructuring and new organization and spatiality dynamics. In despite of the fact that the net relationships are not new, the study of their processes are relevant currently. In some specific spatialities the increasing importance of agrindustrial integration is highlighted, connected to the CAIs and familiar agrindustries. This way, the research aimed to distinguish and analyze the establishment and presence of production nets that coordinate and organize the productive processes in the rural space through vertical and horizontal relationships. The empirical referent was the town of Caibi in the state of Santa Catarina. The set of theoretical, methodological, and conceptual approaches led to a dialectical analysis and a systemic methodology. Different data collection techniques have been applied for the investigation. The conceptual thought conveyed to the terminology net and its current diffusion, as well as the establishment of nets in Brazilian agriculture, its processes and dynamics for the restructuring, approaching different types of nets and the implications for the involved participants. The modernization process in agriculture, from 1960, increased socio-economic inequality among participants, products, and nets. It has also caused the increase of rural exodus, making visible the structures and products specificities. This process led to new ways of net production in the vanguard of the 21st Century, due to the restructuring of the capitalist production mode. Different participants, products, and nets develop relationships through exogenous and endogenous paths, willing to enable the production system. The first makes the vertical spatiality, resulting into production increase and, consequently influencing the economic growth with innovations that, to a certain extent, enable the social group to stay in the rural area. A production mode integrated to the competitive market and cheap workforce exploitation contribute to the market fragility. The second is set horizontally and characterized by trusting bonds, learning, and innovation; it preserves the autonomy of the rural participant constituted by their know-how and culture. These nets might contribute for possible development ways simultaneously approaching welfare based on social, environmental, and economic harmony.